Interplay between extracellular vesicles and allergic diseases: Current insights and future perspectives - Jia Wu; Yan Wang; Yuqing Wang; Jiawei Ribaudo; Shu Li; Shunyan Hu; Maolin Tang; Yongliang Chen; Yan Long (Interdisciplinary Medicine)
Abstract The field of extracellular vesicle (EV) research has rapidly evolved, revealing their significant roles in various biological processes and clinical applications. Allergic diseases are prevalent immunological disorders characterized by exaggerated hypersensitivity reactions to allergens, leading to diverse clinical manifestations that can severely impact quality of life. Recently, studies have underscored the pivotal role of EVs in allergic conditions, including asthma, allergic rhinitis, and atopic dermatitis. In this review, we provide a comprehensive overview of recent advances in the separation and characterization of EVs, their roles in allergic diseases, and their diagnostic value as biomarkers. Additionally, we explore the therapeutic potential of EVs for the treatment and prevention of allergic conditions. Overall, the emerging insights into EVs present promising opportunities for enhancing the diagnosis, treatment, and management of allergic diseases.